Efeitos da intensificação e integração como estratégia para o manejo sustentável das pastagens nos sistemas de produção de bovinos de corte da raça Nelore: produtividade da forragem, desempenho animal e consumo alimentar - Pasquini Neto, Rolando (2022)
Strategies to intensify agricultural beef systems are recommended to meet the growing world demand for food, as they increase pasture quality production and animal performance, diluting GHG emissions by the products generated. This study evaluated the effect of intensification in different grazing systems of beef cattle production on pasture and animal performance. The experiment was conducted from September 2019 to September 2020 at Embrapa Southeast Livestock, São Carlos, SP. Forty Nellore bullocks (375±30 kg and 22.2±0.7 months of age) were randomly distributed in five different production systems (8 animals/system), with two area replications (10 experimental units), being: 1) intensively managed and irrigated Megathyrsus maximus cv. Tanzania pasture with a high stocking rate, overseeded in the dry season with Avena byzantina and Lolium multiflorum (IAL); 2) intensively managed rainfed Megathyrsus maximus cv. Tanzania pasture with a high stocking rate (SAL); 3) intensively managed rainfed pasture with a mix of Urochloa brizantha cv. Marandu and Urochloa decumbens cv. Basilisk with a moderate stocking rate (SML); 4) intensively managed silvopastoral system with Urochloa decumbens cv. Basilisk pasture and Brazilian native trees (350 trees/ha) with moderate stocking rate (SSP); and 5) extensively managed rainfed degraded pasture with a mixture of Urochloa brizantha cv. Marandu and Urochloa decumbens cv. Basilisk with a low stocking rate (DEG). All pastures were subjected to stocking rate adjustments by the “put-and-take” technique, managed under continuous grazing for DEG and rotational grazing for IAL, SAL, SML and SSP with grazing cycles of 36 days. All pastures, except DEG, received liming and corrective fertilization with P, K, S and micronutrients and fertilizers. Pastures in IAL and SAL were fertilized, respectively, with 600 and 400 N-urea/ha/year. Pastures in SML and SSP received 200 kg N-urea/ha/year. Animals from all systems received ad libitum mineral-protein supplement containing NH4NO3. Pasture samples were collected to assess forage production and quality. The animals were weighed at the beginning of the experiment and monthly until the time of slaughter to estimate performance. Markers (TiO2 and NDFi) were used during the seasons to estimate voluntary feed intake and, subsequently, feed efficiency. Data were analyzed using SAS (SAS Inc., Cary, NC, USA), considering the fixed effects: systems, climatic seasons of the year and the interaction between them. There were periods characterized by intense water deficit, reducing the productive potential of the pastures. The best pasture results were in IAL systems, followed by SAL and SML, with better yields and forage quality, which increasing intake, feed efficiency, animal performance and productivity per area, when compared with SSP and DEG; resulting in better use of the crude protein supplied (pasture+supplement). Due to the interaction system*season and the (severe) water deficit that occurred, it was possible to observe that the best results were associated with the systems that presented the best production and quality of the pasture, in addition to animal performances in the dry period of the year.